Estudo do potencial de riscos de inundações nas microbacias da cidade de Rondonópolis, Mato Grosso - Trassi, Jaqueline da Silva (2015)
The main objective of this study was to understand the nature and potential of flooding in the catchments of the urban sprawl of Rondonópolis. Thus, to achieve it was decided to conduct a historical review on the occurrence of floods in the watersheds of the urban area of Rondonópolis. And analyze the relationship of these episodes with the same level of urbanization, classify and map the flood risk areas in these watersheds, and to evaluate the correlation of the level of change / soil sealing thereof with the occurrence of floods promoted to heavy rain. Thus, to achieve these specific objectives were used various research techniques, such as desk research and intensive observation (via structured interviews and unstructured) on the occurrence of floods in the city. Hydrologic modeling implemented via geographic information systems (GIS) to assess the natural propensity of urban watersheds to flooding processes and estimated volumes disposed of by them from the occurrence of heavy rains of 24, using for this purpose, the method "CN "developed by the Soil Conservation Service (SCS). Fieldwork performance and interpretation of high-resolution images to identify, characterize, classify and map areas with flood risk in the city following the methodology proposed by IPT (Institute for Technological Research, 2007). Climate analyzes to know the variability and intensity of rainfall in the basin from the Monteiro proposal (1976) Gumbel (1941). The main results it was found that despite the floods is an old problem that has occurred more frequently in recent years in Rondonópolis the government does not even keep records on them, let alone a program to find solutions for it. The waterproofing level in most watersheds analyzed is already very high (above 80%), and therefore heavy rains of 24 low-volume and high frequency can now promote the occurrence of floods in the same; even in relation to the rains there was the analysis of the climatic rhythm and perception of residents both intense and concentrated rainfall (source convective processes) as the light and continuous (caused by frontal systems) can promote the occurrence of episodes flooding in urban watersheds of Rondonópolis. And in the five watersheds studied met flood risk areas ranging from low to very high risk. Soon the study said what is proposed, revealed that the rains convective nature and high intensity are the main responsible for the occurrence of episodes of flooding in urban area of the city of Rondonópolis, which is mainly due to high soil sealing index their watersheds, driven by real estate capital city, which causes serious trouble to the population residing on the banks of these rivers and streams in the rainy season.